2022
DOI: 10.1021/jacs.1c13299
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Palladium-Catalyzed Radical Migratory Mizoroki–Heck Reaction Enables C2-Alkenylation of Carbohydrates

Abstract: Excited-state palladium catalysis has emerged as a promising strategy for developing novel and valuable reactions. Herein, we report the first excited-state Pd-catalyzed 1,2-radical migratory Mizoroki−Heck reaction that enables C2-alkenylation of carbohydrates using readily available 1-bromosugars and alkenes. The reaction tolerates a wide variety of functional groups and complex molecular architectures, including derivatives of natural products and marketed drugs. Preliminary mechanistic studies and DFT calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 65 publications
2
37
0
1
Order By: Relevance
“…The same authors have also recently reported the application of this strategy to a Mizoroki‐Heck reaction to achieve the C‐ 2‐selective alkenylation of carbohydrates [69] …”
Section: Deoxygenative C−h Bond Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…The same authors have also recently reported the application of this strategy to a Mizoroki‐Heck reaction to achieve the C‐ 2‐selective alkenylation of carbohydrates [69] …”
Section: Deoxygenative C−h Bond Formationmentioning
confidence: 99%
“…This exists in equilibrium between species 88, where the Pd is directly bonded to C-1 (forming a covalently bonded Pd II The same authors have also recently reported the application of this strategy to a Mizoroki-Heck reaction to achieve the C-2-selective alkenylation of carbohydrates. [69]…”
Section: Via Photochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors have also recently reported the application of this strategy to a Mizoroki-Heck reaction to achieve the C2-selective alkenylation of carbohydrates. [56] [Ir(ppy) 2 (dtbbpy)]PF 6 (2 mol%) blue LEDs (λ max = 455 nm) H 2 O (100 equiv.)…”
Section: Scheme 31 Deoxygenation Of Benzylic Alcohols Via B-scissionmentioning
confidence: 99%
“…Saccharide and nucleosides are fundamental biomolecules possessing several hydroxy groups, thus representing ideal targets for the application of late-stage deoxyfunctionalisation strategies. Although some advancements have been made in this area, [55][56]69] there is still a lack of general methodologies that can be applied for selective nucleoside derivatisations. We believe that at the current pace of innovation, these challenges will be tackled in the not-so-distant future.…”
Section: ) Selective Saccharide and Nucleoside Derivatisationsmentioning
confidence: 99%